E-Commerce Boom and Consumer Culture amidst COVID-19 Pandemic: Delineating Indonesia’s Purchasing Pattern (Global Focus, 2022)
Global trade transformation and technological advancement drive business sector into another level we have never imagined and alter people’s daily lifestyle. However, with the occurrence of global pandemic, the world is forced to make a few steps backwards as the economy in most countries see a downturn. Surprisingly, e-commerce set a new adoption of business pattern and lifestyle, and even pushes consumerism to leap forward as people comply with stay-at-home measures. COVID-19 crisis has indeed caused a structural shift towards digital commerce, but the cultural impact is just as powerful.This study would like to delineate particular cases of e-commerce and retail development in Indonesia through mapping consumers’ purchasing pattern as well as current challenges for both people and businesses.The findings suggest that culture can affect business in terms of segments, choices based on latest trends and common belief. In Indonesian case, segmentation is shifting from travel to home-based activities and interest. Yet, preferences on specific trends and lifestyle remain unchanged, for example, younger generation inclination to products of Korean popular culture and products with halal certification. This pinpoints that consumer behaviour and cultural background have to be seriously taken into account for businesses to develop. Albeit it is crucial for business players to turn their attention to this, government has to be able to encourage the growth of the overall landscape by providing an ease into business environment through physical and digital infrastructure assistance in order to create competitive and inclusive milieu in this digital economy era. Keyword(s): e-commerce, business, culture, purchasing pattern, COVID-19 pandemic.